Effect of drying time, bean depth and temperature on free amino acid, peptide-N, sugar and pyrazine concentrations of Malaysian cocoa beans - Hashim, Puziah; Selamat, Jinap; Muhammad, Kharidah; Ali, Asbi (Society of Chemical Industry (SCI), 1999)
The effect of drying time on free amino acid, peptide-N, sugar and pyrazine concentrations as well as the influence of bean depth and temperature on these compounds during cocoa drying was studied. Drying time, bean depth and temperature significantly decreased the concentration of free amino acids, peptide-N, total reducing sugars and sucrose and increased the concentration of trimethyl-, tetramethylpyrazine and total pyrazines in cocoa beans. The best drying treatment was obtained at the combination of bean depth/drying temperature of 8.3 cm/40°C. This was based on the fact that it produced significantly high concentrations of hydrophobic free amino acids, peptide-N and total reducing sugars and significantly low concentration of trimethyl-, tetramethylpyrazine and total pyrazines. Drying treatment of 1.5 cm/60°C significantly produced the lowest concentration of free amino acids, peptide-N and total reducing sugars and the highest concentration of pyrazines.